Looking Beyond Cash Transfers for Optimizing Poverty Reduction and Livelihood Sustainability in Rural Ghana: Comparative Analysis of Two Social Policy Interventions Against Poverty. Issue 1 (3rd April 2020) - Adjei, Prince Osei‐Wusu; Adjei, Joyce Osei; Serbeh, Richard
Abstract : In this article, we argue that, if the poverty reduction inroads recorded from the declaration of the Millennium Development Goals could be optimized and sustained particularly in rural areas experiencing higher incidence of poverty and livelihood vulnerabilities, policymakers and development practitioners ought to look beyond cash transfer measures to embrace skills and technology transfer policies and programs. This approach has a greater tendency of creating appropriate context for the empowerment and enhancement of the production capacities of the poor in ways that guarantee their independence to engage in self‐help initiatives and resilient local livelihoods. This conclusion is drawn from comparative study outcomes of two Government of Ghana social policies for poverty reduction, namely—the Livelihood Empowerment against Poverty and the Rural Enterprise Program. 摘要: 本文中我们主张, 如果千年发展目标(MDGs)宣言中记录的减贫进展能被优化并持续下去, 尤其是在贫困程度、生计脆弱性更高的乡村社区, 那么政策制定者和发展从业人员应长远看待用于拥护技能与技术转移政策及相关计划的现金转移支付手段。该措施更可能以保障贫困人口独立参与自助倡议、保障具备弹性的地方生计等方式, 为贫困人群生产能力的赋权及提升创造适宜环境。通过对加纳政府用于减贫的两个社会政策进行比较研究, 即对抗贫困的生计赋权(LEAP)和农村企业计划(REP), 得出了上述结论。 Resumen: En este documento argumentamos que, si las incursiones de reducción de la pobreza registradas en la declaración de los Objetivos de Desarrollo del Milenio (ODM) pudieran optimizarse y sostenerse particularmente en las áreas rurales que experimentan una mayor incidencia de pobreza y vulnerabilidades de los medios de vida, los responsables políticos y los profesionales del desarrollo deberían considerar más allá de las medidas de transferencia de efectivo para adoptar habilidades y políticas y programas de transferencia de tecnología. Este enfoque tiene una mayor tendencia a crear un contexto apropiado para el empoderamiento y la mejora de las capacidades de producción de los pobres de manera que garanticen su independencia para participar en iniciativas de autoayuda y medios de vida locales resilientes. Esta conclusión se extrae de los resultados del estudio comparativo de dos políticas sociales del Gobierno de Ghana para la reducción de la pobreza, a saber: el Empoderamiento de los medios de vida contra la pobreza (LEAP) y el Programa de empresas rurales (REP).